The relationship between general and game based performance in team-handball - Wagner, H.; Pfusterschmied, J.; Orwat, M.; von Duvillard, S. P.; Müller, E. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Team-handball is a fast pace game of defensive and offensive actions including specific movements of passing and throwing a ball, jumping, blocking, tackling, fast accelerations and change of directions. However, team-handball performance is mostly measured using standardized endurance, strength and agility tests (Gorostiaga et al., 2005) that do not reflect actual performance in team-handball. Consequently, the aim of the study was to measure and compare general and game based performance in teamhandball. Methods: 15 experienced team-handball players performed a game based performance test (GBPT) (Wagner et al., 2014), an incremental treadmill-running test, a 30m sprinting test, lower and upper body strength test, and a counter movement jump (CMJ) test. We measured peak oxygen uptake (VO2peak), utilizing portable metabolic system (Cosmed K4B2), blood lactate concentration (BLCpeak) (EKF, Biosen C), heart rate (Polar, Kempele, Finland), sprinting time, and offensive and defensive time actions (Inmotion LPM-system, Abatec, Austria), ball velocity and jump height during a jump throw (PeakMotus, Vicon Peak, UK), isometric leg force and shoulder and trunk rotation torque (ISOMED, D&R Ferstl, Germany), as well as jump height in the CMJ (AMTI, Watertown, USA). Relationship between general and game based performance was determined utilizing Pearson Product-Moment correlation. Results: We found correlation (r>.55, P <.05) between sprinting times in the general and GBPT as well as offensive time actions in the GBPT, between shoulder and trunk rotation torque, and between jump height in the CMJ and general sprinting time (r < -.55). Team-handball players with greater body mass reached a lower VO2peak in the GBPT, a greater starting time (0-15m) in the general sprint test and a lower jump height in the CMJ. Surprisingly, we also found correlation between the jump height in the CMJ and jump throw and the VO2peak in the GBPT and no correlation between the VO2peak in the GBPT and the incremental treadmill-running test. Discussion: In conclusion, we found that standardized tests measuring general performance of endurance, strength and agility are only marginally suitable to determine specific teamhandball performance in experienced team-handball players. Whereas, sprinting tests and a counter movement jump test were appropriate to determine team-handball game based agility and speed no relationship between general endurance and strength, or teamhandball game based performance was found.